Revision Stapedotomies: The Role of Periprosthetic Scar Tissue Formation in the Development of Unsatisfactory Hearing Results after Stapedotomy - Polony,Gábor (2022)
Abstract Introduction Revision stapes surgeries are difficult to perform, and their audiological results are inferior to primary surgeries. Objective Our goal was to identify the most common and most influential postoperative reasons that cause persistent air-bone gap (ABG) after the primary surgery. Our focus was concentrated on the mechanical dysfunctions in the middle ear, with special regard to postoperative adhesion formation. Methods We performed a retrospective case series study with 23 cases that underwent revision stapedotomies. Results A significant improvement was seen in ABG and air conduction levels after surgery. The periprosthetic adhesion formation was seen in 65% of the cases, and it was the primary cause behind the unsatisfactory hearing result in 30% of cases. There was no significant difference in the level of persistent ABGs after the primary surgery, in case of the intratympanic adhesion presence, compared with the presence of other surgical failures. Concerning hearing and ABG gain after revision surgery, the non-inferiority of the negative effect associated with adhesion was shown compared with the other reasons. Conclusion The revision stapedotomy is an efficient treatment option in case of persistent ABG. Periprosthetic adhesions are the most common intratympanic reasons for compromised audiological outcomes after stapedotomy.